Whole-genome analysis of natural interspecific recombinant between bovine alphaherpesviruses 1 and 5 - Romera, Sonia Alejandra (2022)
Bovine alphaherpesviruses 1 and 5 (BoHV-1 and BoHV-5) are closely related viruses that co-circulate in South America and recombine in the field. The complete genomes of three natural gB gene recombinant viruses between BoHV-1 and BoHV-5 were obtained by Illumina next-generation sequencing. Complete genome sequences of the three recombinant strains (RecA1, RecB2, and RecC2) have a similar size of approximately 138.3kb and a GC content of 75%. The genome structure corresponds to herpesvirus class D, with 69 open reading frames (ORFs) arranged in the same order as other bovine alphaherpesviruses related to BoHV-1. Their genomes were included in recombination network studies indicating statistically significant recombination evidence both based on the whole genome, as well as in the sub-regions. The novel recombinant region of 3074 nt of the RecB2 and RecC2 strains includes the complete genes of the myristylated tegument protein (UL11) and the glycoprotein M (UL10) and part of the helicase (UL9) gene, and it seems to have originated independently of the first recombinant event involving the gB gene. Phylogenetic analyzes performed with the amino acid sequences of UL9, UL 10, and UL11 indicated that RecB2 and RecC2 recombinants are closely related to the minor parental virus (BoHV-1.2b). On the contrary, RecA1 groups with the major parental (BoHV-5), thus confirming the absence of recombination in this region for this recombinant. One breakpoint in the second recombinant region lies in the middle of the UL9 reading frame, originating a chimeric enzyme half encoded by BoHV-5 and BoHV-1.2b parental strains. The chimeric helicases of both recombinants are identical and have 96.8 and 96.3% similarity with the BoHV-5 and BoHV-1 parents, respectively. In vitro characterization suggests that recombinants have delayed exit from the cell compared to parental strains. However, they produce the similar viral titer as their putative parents suggesting the accumulation of viral particles for the cell exit delayed on time. Despite in vitro different behavior, these natural recombinant viruses have been maintained in the bovine population for more than 30 years, indicating that recombination could be playing an important role in the biological diversity of these viral species. Our findings highlight the importance of studying whole genome diversity in the field and determining the role that homologous recombination plays in the structure of viral populations. A whole-genome recombinant characterization is a suitable tool to help understand the emergence of new viral forms with novel pathogenic features.